Successful Treatment of Multiple Alopecia Areata With Contact Immunotherapy: Supportive Usage of Oral Antihistamine and Topical Corticosteroid - Maya Kaga-Kamijo; Shigaku Ikeda (Dermatology, 2017)
Contact immunotherapy using diphenylcyclopropenone (DPCP) is a commonly used first-line therapeutic technique for patients with alopecia areata (AA). We present here a successful immunotherapy for AA female case with atopic diathesis, using oral antihistamine and topical corticosteroid supportively on DPCP. Courses of clinical and laboratory findings suggested that indirect effect to allergic inflammation by antihistamine drugs contributed to AA regression in our case.